Enhanced Photodegradation Ability of Antibiotics with Composite Based on V2O5 under Visible Light - Chi, Nguyen Thi Phuong Le; Vuong, Truong Thi; Lan, Nguyen Thi; Duc, Truong Cong; Tam, Truong Thanh; Quoc, Nguyen Tri; Luong, Nguyen Van; Phuong, Tran Thi Thu; Mai, Nguyen Vu Ngoc (VNU Journal of Science: Natural Sciences and Technology; Vol 41 No 3DO - 10.25073/2588-1140/vnunst.5617, 2025)
In this paper, V 2 O 5 combining with g-C 3 N 4 were obtained to reduce charge recombination rate between electrons and holes in semiconductors. X-ray photoelectron spectroscopy (XPS) results indicated certain interaction between V 2 O 5 and g-C 3 N 4 in the V 2 O 5 /g-C 3 N 4 heterojunction. In addition, the reducing in recombination of photogenerated electrons and holes was confirmed via the photoluminescence (PL) spectrum. The photocatalytic activities of the as-synthesized materials were investigated by the degradation of tetracycline hydrochloride (TC) under visible light. The V 2 O 5 /g-C 3 N 4 heterojunction is more active than pure V 2 O 5 and g-C 3 N 4 . The TC degradation efficiency by V 2 O 5 /g-C 3 N 4 photocatalyst under visible light was 82.18% after 180 minutes. The improvement in photocatalytic activity of V 2 O 5 /g-C 3 N 4 can be attributed to the reduction of recombination rate of photogenerated electron and hole pairs.